The Analysis of Good Organization Governance to the Leadership and Regeneration Effectiveness in Muhammadiyah Islamic Mass Organization - Jaenudin, Jaenudin; Fauziana, Eva (Adpebi International Journal of Multidisciplinary Sciences, 2022)
Muhammadiyah having basic problems but crucial related to its regeneration. Internal thought among the senior leaders in its organization worried of the young generation who will replace their positions to run and lead the organization in the future. 60 million members spread all over Indonesia (per-2019) is a such a huge number of members, but seems limited for future regeneration who will seriously giving contribution in this mass organization. This study researches and analyzes its good organization governance, whether can effectively having leadership functions, and how the social perspectives to  its effectiveness and captures what young generations’ perception on it. This research distributed questioners to 217 respondents, and using SEM (PLS) in analyzing the data. Three major variables on this study are good organization governance, leadership and regeneration.  The limitation of the study was the respondents are mostly domicile in Bekasi areas, so it still not captured yet the big picture of organization as a whole. The result of this study show the strong correlation between good organization governance, leadership effectiveness and young generations perceptions on Muhammadiyah as an Islamic mass organization.